The sequential development of jaw and lip control for speech. - Green, Jordan R.; Moore, Christopher A.; Reilly, Kevin J. (Journal of Speech, Language & Hearing Research, 2002)
Vertical displacements of the upper lip, lower lip, and jaw during speech were recorded for groups of 1-, 2-, and 6-year-olds and adults to examine if control over these articulators develops sequentially. All movement traces were amplitude- and time-normalized. The developmental course of upper lip, lower lip, and jaw control was examined by quantifying age-related changes in the similarity of each articulator's movement patterns to those produced by adult subjects and by same-age peers. In addition, differences in token-to-token stability of articulatory movement were assessed among the different age groups. The experimental findings revealed that 1- and 2-year-old children's jaw movements were significantly more adult-like than their upper and lower lip movements, which were more variable. In contrast, upper and lower lip movement patterns became more adult-like with maturation. These findings suggest that the earliest stages of speech motor development are constrained by the nonuniform development of articulatory control, with the jaw preceding the lips. The observed developmental patterns suggest that the properties of the oral motor control system significantly influence the pattern of speech sound acquisition. Reprinted by permission of the publisher.